Global, regional, and national burden of ischemic heart disease in youths and young adults aged 15–39 years in 204 countries/territories, 1990–2021: a systematic analysis of global burden of disease study 2021 - Sun, Weixin; Li, Peijie; Ni, Qimeng; Pan, Renyou; Gu, Tingting; Song, Xiaolong; Liu, Ping; Gu, Yuexing (Frontiers in Cardiovascular Medicine, 2025)
BackgroundIschemic heart disease (IHD) remains a global public health challenge. This study explores global trends in IHD burden among youths and young adults aged 15–39 years from 1990 to 2021.MethodsData were obtained from the 2021 Global Burden of Disease (GBD) study. Estimated annual percentage change was used to assess trends in age-standardized prevalence rate (ASPR), incidence rate (ASIR), mortality rate (ASMR), and disability-adjusted life years (DALYs). Risk factors were analyzed globally and by socio-demographic index (SDI) regions. Bayesian age-period-cohort models predicted trends over the next 30 years.ResultsFrom 1990 to 2021, IHD-related mortality and DALYs declined overall, while prevalence and incidence increased. The largest increases in ASPR, ASIR, ASMR, and DALY rates were observed in middle-SDI regions. Geographically, Asia bore the heaviest burden, whereas high-income North America showed the greatest decreases in prevalence and incidence. In 2021, Oceania had the highest IHD-related deaths and DALYs, with Lesotho exhibiting the greatest rise in ASMR and DALY rates. The IHD burden rose with age, peaking in the 35–39 years group, and was higher in males. Major risk factors included high low-density lipoprotein cholesterol, smoking, and high systolic blood pressure. Projections suggest a global decline in IHD burden, with decreasing incidence and deaths across both sexes by 2050.ConclusionsWhile mortality and DALYs have decreased over the past 30 years, prevalence and incidence of IHD in youths and young adults have increased. The burden is projected to decline, emphasizing the need for targeted interventions, particularly in males aged 35–39 years, based on regional epidemiological patterns and risk factors.